Oxidative Stress and Aberrant Programmed Cell Death Are Associated With Pollen Abortion in Isonuclear Alloplasmic Male-Sterile Wheat - Liu, Zihan; Shi, Xiaoyi; Li, Sha; Zhang, Lingli; Song, Xiyue (Frontiers in Plant Science, 2018)
Cytoplasmic male sterility is crucial for the utilization of hybrid heterosis and it possibly occurs in parallel with tapetal programmed cell death (PCD) and oxidative metabolism responses. However, little is known about the mechanisms that underlie pollen abortion in wheat. Therefore, we obtained two isonuclear alloplasmic male sterile lines (IAMSLs) with Aegilops kotschyi and Ae. juvenalis cytoplasm. Compared with the maintainer line, cytochemical analyses of the anthers demonstrated that the IAMSLs exhibited anomalous tapetal PCD and organelles, with premature PCD in K87B1-706A and delayed PCD in Ju87B1-706A. We also found that the dynamic trends in reactive oxygen species (ROS) were consistent in these two IAMSLs during anther development and they were potentially associated with the initiation of tapetal PCD. In addition, the activities of ROS-scavenging enzymes increased rapidly, whereas nonenzymatic antioxidants were downregulated together with excess ROS production in IAMSLs. Real-time PCR analysis showed that the expression levels of superoxide dismutase, catalase, and ascorbate peroxidase genes, which encode important antioxidant enzymes, were significantly upregulated during early pollen development. Thus, we inferred that excessive ROS and the abnormal transcript levels of antioxidant enzyme genes disrupted the balance of the antioxidant system and the presence of excess ROS may have been related to aberrant tapetal PCD progression, thereby affecting the development of microspores and ultimately causing male sterility. These relationships between the mechanism of PCD and ROS metabolism provide new insights into the mechanisms responsible for abortive pollen in wheat.